An Exploration of Problematic Smartphone Use among Chinese University Students: Associations with Academic Anxiety, Academic Procrastination, Self-Regulation and Subjective Wellbeing. - Yang, Zeyang; Asbury, Kathryn; Griffiths, Mark D. (International Journal of Mental Health & Addiction, 2019)
Over the past decade, there have been an increasing number of studies that have investigated problematic and/or 'addictive' smartphone use. The present study explored the prevalence and correlates of problematic smartphone use (PSU) among Chinese university students. Few studies have investigated relationships between PSU and factors such as academic anxiety, academic procrastination, self-regulation, and subjective wellbeing. The present study proposed and tested a hypothetical model of relationships between PSU and these factors. A total of 475 Chinese university students completed a paper-based survey during class breaks. The survey comprised a battery of psychometric scales translated into Chinese translations examining the study variables (i.e., academic anxiety, academic procrastination, self-regulation, life satisfaction, and PSU). Path analysis was applied to test the hypothetical model. A good model fit was found (CFI = 1.00, RMSEA = 0.008), in which PSU predicted academic procrastination (β = 0.21, p < 0.001) and academic anxiety (β = 0.18, p < 0.01). Also, self-regulation predicted PSU (β = − 0.35, p < 0.001), academic anxiety (β = − 0.29, p < 0.001), academic procrastination (β = 0.23, p < 0.001) and life satisfaction (β = 0.23, p < 0.001). PSU mediated the relationships between self-regulation, and both academic anxiety and academic procrastination. The present study enhances our understanding of the role of problematic smartphone use in relation to academic behaviour, mental health and wellbeing of college students.